Diseño de un sistema de gestión integrado QHSE, en la empresa ICICO S.A.S. en el sector de hidrocarburos en Casanare (Colombia) (2015)
The management of ICICO SAS, as a company, seeks to obtain greater recognition and be more competent in the medium to which it belongs, for which it seeks to integrate its Management Systems: ISO 9001: 2008 Quality Management System, ISO 14001: 2004 System of Environmental Management and OHSAS 18001: 2007 Occupational Health and Safety System, demonstrating its greatness of leadership and work opportunity to the community, increasing its market expectations by improving each of its activities carried out in civil works. The responsibility of the company is to preserve, preserve and improve the health of workers, provide satisfaction to customers, preserve the environment, therefore, must prevent any damage to the health of people, derived from the conditions of work, protect the person (workers and external personnel) against the risks related to physical, chemical, organic, mechanical and other agents including the risks that may cause emergencies, eliminate or control the agents harmful to health in the workplace, protect workers and the population against health risks arising from the production, storage, transportation, sale, use or disposal of substances dangerous to public health, meet the requirements and expectations of the client, care for and preserve the environment , not polluting bodies of water, reducing the use of electricity and water, guarantee the customer executed it n of each of the projects. With the implementation of this Integrated Management System, it will be possible to minimize the number of risks, mitigate negative environmental impacts and non-compliance on the part of clients, as well as to ensure that all personnel and other interested parties can access and put into practice requirements and other obligations that the standards require. The design of the integrated management system allows ICICO S.A.S. have greater credibility and opportunity at the time of participating in a bidding process, facilitating and consolidating their participation in projects in the hydrocarbon sector.